Role and mechanism of pumilio homolog 1 in hypoxia/reoxygenation induced injury of human renal tubular epithelial cells - Sheng-guo Hu; Yi Guo; Chao Yuan; You-kong Li; Min Wang; Min Zhu (Editorial Department of Journal of Clinical Nephrology, 2024)
Objective To explore the role and mechanism of pumilio homolog 1 （PUM1） in hypoxia/reoxygenation induced cell injury in human renal tubular epithelial cells （HK-2）. Methods A hypoxia/reoxygenation （H/R） model of HK-2 cells was established in vitro. PUM1 expression was knocked down through small interfering RNA （siRNA）. Cells were randomized into three groups of control， hypoxia/reoxygenation （H/R） and H/R+siRNA. Western blot （WB） method was used for detecting the expression level of PUM1 protein. Cell Count Kit 8 （CCK-8） was employed for detecting cell viability. Hydrogen peroxide （H2O2）， malondialdehyde （MDA） and superoxide dismutase （SOD） were used for evaluating the levels of oxidative stress. Flow cytometry was utilized for detecting the level of cell apoptosis. Results As compared with control group， protein expression level of PUM1 in H/R 3 h group （1.76 ± 0.11 vs 0.98 ± 0.05）， H/R 6 h group （2.89 ± 0.14 vs 0.98 ± 0.05） and H/R 12 h group （3.78 ± 0.08 vs 0.98 ± 0.05） gradually spiked with the prolongation of hypoxic time. As compared with H/R group， knocking down the expression of PUM1 significantly improved the cell viability （73.67 ± 3.42 vs 29.60 ± 2.94）， oxidative stress [H2O2:（13.53 ± 0.85）μmol/L vs （22.43 ± 1.12）μmol/L， MDA: （16.03 ± 0.70）μmol/L vs （31.20 ± 1.50）μmol/L， SOD: （34670 ± 1800）U/L vs （5730 ± 1220）U/L] and apoptotic level [（14.89 ± 1.65）% vs （39.71 ± 1.94）%] after H/R in H/R+si-PUM1 group. Conclusion PUM1 is up-regulated in H/R induced HK-2 cells and its inhibition may alleviate H/R injury through reducing oxidative stress and lowering cell apoptosis levels.